Effect of Dietary Cannabis sativa L. Residue Supplementation on Meat Quality and Flavor-Enhancing Free Amino Acids in Broiler Chickens - Yusup Sopian; Katatikarn Sahatsanon; Apinya Satsook; Chaiwat Arjin; Korawan Sringarm; Chompunut Lumsangkul; Panneepa Sivapirunthep; Chanporn Chaosap (Animals, 2025)
< 0.05). In conclusion, CR supplementation improves the flavor and nutritional value of broiler meat and is a potential alternative to conventional feed additives.
Keywords: Animal Nutrition and Physiology; Biochemical effects in animals; GABA and Rice Research